New record of the Ponerine ant Buniapone amblyops (Emery, 1887) (Hymenoptera: Formicidae) from Nepal - Subedi, Indra Prasad (Nepalese Journal of Zoology, 2021)
Buniapone Schmidt & Shattuck 2014 is a monotypic and morphologically distinct hypogeic ant genus found only in Southern and Southeast Asia. The Ponerine ant Buniapone amblyops (Emery 1887) has been recorded for the first time from Nepal. The specimen was hand-collected in Pokhara (28.21361111 N, 83.97222222 E, 840 m asl) from animal dung on the ground. Morphological characteristics of Nepalese B. amblyops worker, distribution, and ecology are discussed.